The structure of the sedimentary complex of the Middle and South Caspian depressions (Azerbaijan sector) - Yusubov, N.P.; Guliyev, I.S. (Geofizicheskiy Zhurnal, 2021)
The high degree of knowledge of the upper horizons of the sedimentary cover of the Middle and South Caspian depressions, given an insufficient increase in hydrocarbon reserves, leads to the need for a detailed approach to the search for oil and gas deposits in deep-seated sediments (over 6 km). During the geological interpretation of new highly informative seismic data, as well as data of deep drilling and petrological core studies, there were revealed obvious shortcomings in the concepts of the origin and evolution of the Middle and South Caspian depressions. These ideas misinterpret evolution, especially the South Caspian Basin, which is characterized by a number of unique features: very thick sedimentary cover (up to 22 km), extremely high sedimentation rate, low heat flow and reservoir temperatures, abnormally high pore and reservoir pressures, high clay content of the section, etc. The main purpose of the study was to elucidate the regional structure and features of the dissection of the sedimentary cover of the Middle and South Caspian depressions, the conditions of occurrence and distribution of facies and thicknesses of individual complexes of deposits. The paper analyzes the results of some previous studies of the geological structure of the Middle and South Caspian depressions based on the data of deep seismic sounding, seismological and gravimetric observations. We consider the main conclusions of these studies, about the geological structure of the sedimentary complex of the region’s, very outdated and subject to revision. The results of seismic stratigraphic analysis of seismic data allowed the authors to identify new data about the tectonic structure and express a completely different point of view regarding the structure of the sedimentary cover in the region. The work also touches on the issue associated with the tectonics of the region and the alleged subduction zone here.